Ways of reduction of environmental risks of slag heaps of metallurgical enterprises, Ukraine - Khrutba, Viktoriia O.; Nikitchenko, Julia S.; Кriukovska, Lesya І.; Lukianova, Vitalina V.; Spasichenko, Oksana V. (Kyiv National University of Construction and Architecture, 2021)
The purpose of this work is a quantitative assessment of the level of reduction of environmental risks of slag heaps of metallurgical enterprises with the use of metallurgical slag as an alternative road construction material.Methods. Quantitative analysis of the emergence of the risk of environmental hazard is carried out in accordance with the "Methodology for determining the risks and their adopted levels for the declaration of safety of objects of high danger", which determines the procedure for conducting a hazard analysis and risk assessment of high-risk objects, which is carried out through the definition of the probability of undesirable consequences of accidents on based scripts for their emergence and development. For the risk assessment, a logical-probabilistic hazard response scheme in the form of a "failure tree" is constructed and analyzed, which is a form of an ordered graphical representation of the logical-probabilistic connection of random events that results in an undesirable result. The calculation of road surface design with alternative road-building materials is carried out in accordance with the VBN V.2.3-218-186-2004 "Construction of vehicles. Non-rigid type of road clothes" taking into account the requirements of the GBN V.2.3-218-007: 2012 "Environmental requirements for highways Designing".Results. To determine the main causes of environmental hazards in the dumps of metallurgical combines and the nature of their impact on the environment, a tree of problems has been constructed that allows us to determine the main causes of a high level of environmental hazard and the emergence of hazardous situations, namely, the large volumes of metallurgical waste stored on the territory of dumps. For the dumps around the steel mills in Mariupol a "tree of failure" was built and the probability of occurrence of an ecologically dangerous situation or an accident which is connected with places of storage of metallurgical deposits of PJSC "Azovstal Iron and Steel Works" and PJSC "Mariupol Iron and Steel Works named after Ilyich" is calculated. The risk of the risk of storing slags in the dumps of metallurgical combines of the occurrence of the main event is 0.636. The main environmental hazards are the amount of slag and slag dust in the dump area. Design of road clothing with the use of metallurgical slags. The content of metallurgical slag in the proposed designs of the DO reaches 25 ... 32%. The use of metallurgical slags, which are low-toxic waste, that is, waste of Class IV hazard, in road construction will reduce the level of existing environmental risk, provided the metallurgical slags of consumer properties.Scientific novelty. As a result of the performed research, an effective approach to reduce the environmental risks of slag heats of steel mills was identified through the use of large volumes of slag as an alternative road construction material. The design of road clothing for the construction of roads of different categories and the level of reduction of the ecological risk of the dump impact on the environment and health of the population of the region are determined.Practical significance. The practical application of the proposed approach was made for slag heaps of the metallurgical combines of Mariupol (Ukraine). The level of ecological safety of the region by reducing the amount of metallurgical slags can be increased by 27-30%, which will allow the company to obtain a total ecological and economic effect in the amount of 1.22 million UAH.